2007
DOI: 10.1186/1476-4598-6-39
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel androgen receptor target genes in prostate cancer

Abstract: Background: The androgen receptor (AR) plays critical roles in both androgen-dependent and castrate-resistant prostate cancer (PCa). However, little is known about AR target genes that mediate the receptor's roles in disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 68 publications
5
61
0
Order By: Relevance
“…In addition, the ARBSs are also relatively evenly distributed at distal enhancer regions within 25kb up or downstream of the TSS. This result is in agreement with several other reports that ARBSs are not limited to the proximal promoter immediately upstream of the transcriptional start sites (Jariwala, et al, 2007; Takayama, et al, 2007; Waltering, et al, 2009; Wang, et al, 2007). …”
Section: Resultssupporting
confidence: 94%
“…In addition, the ARBSs are also relatively evenly distributed at distal enhancer regions within 25kb up or downstream of the TSS. This result is in agreement with several other reports that ARBSs are not limited to the proximal promoter immediately upstream of the transcriptional start sites (Jariwala, et al, 2007; Takayama, et al, 2007; Waltering, et al, 2009; Wang, et al, 2007). …”
Section: Resultssupporting
confidence: 94%
“…Thus, enhanced TRPV3 function can indeed explain the allergic and inflammatory manifestations displayed by the affected skin tissues of the mutant rodents. Furthermore, a recent study has identified TRPV3 as a novel target of androgen receptors that displays enhanced expression in response to dihydrotestosterone [25], suggestive a potential link of TRPV3 upregulation in androgenetic alopecia, a common problem that affects approximately 50% of the male population.…”
Section: Discussionmentioning
confidence: 99%
“…Androgens are critical to the normal development, proliferation, and differentiation of prostate epithelial cells and signaling occurs via intracellular AR [23,32]. Recurrent prostate cancer after primary treatment is typically androgen-dependent, and so androgen deprivation therapy is effective in causing a remission of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%